Comparing conventional practices and good agricultural practices: socio-economic impacts on smallholder vegetable farmers in Cambodia - Thangrak, Veu; Lyhour, Hin; Pisidh, Voe; Socheat, Ngy; Socheat, Hill (Asian Journal of Agriculture and Rural Development, 2025)
Vegetable production is essential in Cambodia’s agricultural sector, contributing to sustainable rural livelihoods, domestic demand, and the economy. However, the quality of vegetables remains limited, largely due to improper application of cultivation techniques. In this regard, good agricultural practices (GAP) have been introduced in the country to address this issue. The aim of the study was to determine the factors influencing GAP adoption and income in vegetable farming systems, explore challenges and perceptions related to the CamGAP standard, and compare the economic performance of GAP and non-GAP farmers. The study was conducted in six provinces between January and June 2024, involving interviews with 85 GAP and 60 non-GAP leafy vegetable farmers. A two-sample t-test was used to compare household characteristics and economic outcomes between the two groups. Likert scale surveys evaluated potentials and constraints to vegetable production, while LASSO regression models identified factors influencing GAP adoption. Results indicate that age, GAP application, and total production costs significantly affected farmers’ income. GAP application is notably associated with membership in agricultural cooperatives. The average income was 346.7 USD per 0.1 hectare for GAP farmers and 170.7 USD per 0.1 hectare for non-GAP farmers. GAP application increased incomes and resulted in higher-quality products due to reduced chemical use during cultivation. Strengthening and expanding agricultural cooperatives are essential for promoting wider GAP adoption, increasing rural incomes, and reducing environmental impacts in vegetable production.